The planter's speech to his neighbours & country-men of Pennsylvania, East & West-Jersey : and to all such as have transported themselves into new-colonies for the sake of a quiet retired life : to which is added the complaints of our supra-inferior-inhabitants - Tryon, Thomas, 1634-1703 (Printed and sold by Andrew Sowle in Shoreditch, 1684)
1684 Planter's speech to his neighbors and countrymen of Pennsylvania, East and West Jersey, and to all who had transported themselves into the colonies for the "sake of a quiet retired Life," along with the complaints of "our supra-inferior Inhabitants." The document was printed in London and written by Thomas Tryon. Of note, on the document's page 41, there is a section entitled, "Chap. V, The Complaints of the Birds and fowls of Heaven to their Creator, for the Oppressions and violences most Nations on Earth do offer unto them, particularly the People Called Christians, lately settled in several Provinces in America;" followed on page 72 by the "B[ir}ds Supplication."